2003
DOI: 10.2527/2003.8192199x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein on calpastatin in canine skeletal muscle1

Abstract: The cysteine proteinases, μ-and m-calpain, along with their inhibitor, calpastatin, have been hypothesized to play a role in skeletal muscle protein degradation. Because nutrition has previously been shown to influence the expression of calpastatin, the working hypothesis of this study was that the quantity and source of dietary protein could influence regulation of the calpain system in muscle. The objectives to support this hypothesis were to determine the effects of dietary protein (amount and source) on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Helman et al [65] reported that dogs fed diets containing animal protein (chicken) were better able to control calpastatin-related protein degradation than those fed diets containing corn gluten meal. Further research is necessary to determine whether decreased expression of MYBPC1 and TTN in geriatric dogs fed APB as compared to PPB in this experiment are mechanisms by which this occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Helman et al [65] reported that dogs fed diets containing animal protein (chicken) were better able to control calpastatin-related protein degradation than those fed diets containing corn gluten meal. Further research is necessary to determine whether decreased expression of MYBPC1 and TTN in geriatric dogs fed APB as compared to PPB in this experiment are mechanisms by which this occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Following three 10-min washes, membranes were visualized using enhanced chemiluminescence Western blotting reagents (Amersham Bioscience) and exposure to film (MR; Eastman Kodak, Rochester, NY). The density of bands was quantified by using an Imager Scanner II and ImageQuant TL software [17,18].…”
Section: Immunoblottingmentioning
confidence: 99%
“…After three 10-min washes, membranes were visualized using ECL Western blotting reagents (Amersham Bioscience) and exposure to film (MR, Kodak, Rochester, NY). The density of bands was quantified by using an Imager Scanner II and ImageQuant TL software (Helman et al, 2003;Du et al, 2004).…”
Section: Calpastatin Content Assay By Immunoblottingmentioning
confidence: 99%
“…Calpains are regulated by Ca 2+ concentration and by binding to calpastatin. The expression level of calpastatin is regulated by genetics and nutrients (Geesink and Koohmaraie, 1999;Helman et al, 2003). Calpastatin activity was higher (P < 0.05) in the callipyge muscle than that in the normal muscle (Geesink and Koohmaraie, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation